2017
DOI: 10.1177/2045893217724141
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of macrophage migration inhibitory factor (MIF) and other angiogenic biomarkers profiling in pulmonary arterial hypertension

Abstract: Macrophage migration inhibitory factor (MIF) and 22 a priori selected biomarkers were measured from pulmonary arterial hypertension (PAH) patients. Significant positive correlations were found between MIF and several angiogenic factors suggesting a possible MIF regulation role in PAH angiogenesis and pathobiology, but simultaneously highlighting the biomarkers profiling complexity in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…Even if concentration levels vary greatly in the existing literature, circulating MIF levels have been found to be elevated in several forms of PH/PAH (Table 1). Importantly, these results support the notion that circulating MIF levels could serve, alone or in conjunction with other inflammatory mediators, as a potential biomarker of PAH severity(14,20,35,44,57). Of note, no significant difference in blood levels of the MIF homolog d-dopachrome tautomerase (DDT or MIF-2) between patients with PAH and control subjects without established cardiovascular disease (7.4 ± 2.2 versus 4.6 ± 1.0 ng/mL)(39).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Even if concentration levels vary greatly in the existing literature, circulating MIF levels have been found to be elevated in several forms of PH/PAH (Table 1). Importantly, these results support the notion that circulating MIF levels could serve, alone or in conjunction with other inflammatory mediators, as a potential biomarker of PAH severity(14,20,35,44,57). Of note, no significant difference in blood levels of the MIF homolog d-dopachrome tautomerase (DDT or MIF-2) between patients with PAH and control subjects without established cardiovascular disease (7.4 ± 2.2 versus 4.6 ± 1.0 ng/mL)(39).…”
supporting
confidence: 69%
“…Stefanantoni et al (55) also reported increased MIF levels in idiopathic PAH and SSc-PAH patients with higher NYHA functional classes. More recently, Marshall et al(44) reported significant positive correlations between MIF levels and those of seven angiogenic factors (angiopoietin-1, vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF)-BB, fibroblast growth factor (FGF)-2, epidermal growth factor (EGF), placental growth factor (PLGF), and Dickkopf (DKK)-1) in patients with idiopathic PAH and those with connective tissue diseaseassociated PAH (CTD-PAH) in a cohort of patients enrolled in the FREEDOM C-2 trial. However, the authors did not find any correlation between MIF levels and prognostic markers, such as sixminute walk distance (6MWD) or the composite clinical outcome, in this cohort(44).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Macrophage migration inhibitory factor (MIF), originally identified as a T-cell-derived cytokine that inhibited the random migration of macrophages, has equally been found increased in PAH [ 58 ]. MIF is now considered an important pro-inflammatory mediator secreted by numerous cells including T cells, macrophages/monocytes, ECs, and SMCs that can induce in turn the production of cytokines, such as IL-1β, IL-6, and IL-8.…”
Section: Inflammatory Mediators and Their Effects On Vascular Remomentioning
confidence: 99%
“…Além disso, há citocinas que aumentam concomitantemente com a idade (entendida como elemento de gravidade) enquanto outras diminuem, comportamento não observado em controles pediátricos 29,30 . A proteína MIF, relacionada entre outros aspectos à resposta T helper 2 (Th2), tem amplo efeito biológico em remodelamento vascular, notadamente nos pulmões, estando associada à proliferação de células musculares lisas vasculares e inibição de apoptose em células endoteliais 31,32 .…”
Section: Elementos Inflamatórios No Remodelamento E Na Resposta Vascular Pulmonarunclassified